N,N′-(Ethane-1,2-diyl)dibenzenesulfonamide - Al-Dajani, Mohammad T. M. (International Union of Crystallography, 2011)
In the title compound, C(14)H(16)N(2)O(4)S(2), the dihedral angle between the terminal phenyl rings is 77.07 (13)°. The geometries around the S atoms are distorted tetrahedral, with O—S—O angles of 120.66 (12) and 119.44 (11)°. In the crystal, molecules are stacked in columns along the a axis via intermolecular N—H⋯O and C—H⋯O hydrogen bonds.